2012
DOI: 10.1089/scd.2012.0112
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hyperthermia Promotes and Accelerates Development and Maturation of Erythroid Cells

Abstract: Hyperthermia treatment has at times been associated with increased platelet levels in humans. The heat shock protein HSP70, which can be induced by hyperthermia in megakaryocytes and erythrocytes, was recently shown to protect GATA-1 from degradation and to be required for erythroid differentiation. Based on these findings, we hypothesize that mild hyperthermia (MH), such as fever (39°C), could impact the differentiation of hematopoietic progenitors into erythrocytes and their subsequent maturation. Cell growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Mammalian cells are usually cultured at 37°C in the incubator supplied with 5% of CO 2 unless specific research purpose is required [7]. Previous studies showed that low temperature decreases cell growth rate and affects embryo development [810]; whereas mild heat stress enhances cell proliferation rate and accelerates development [1112]. In addition, the viability for mammalian cells or embryos can be severely affected after long-term treatment at sub-zero temperature [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cells are usually cultured at 37°C in the incubator supplied with 5% of CO 2 unless specific research purpose is required [7]. Previous studies showed that low temperature decreases cell growth rate and affects embryo development [810]; whereas mild heat stress enhances cell proliferation rate and accelerates development [1112]. In addition, the viability for mammalian cells or embryos can be severely affected after long-term treatment at sub-zero temperature [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, low temperature can decrease cell growth rate (Azambuja et al, 1998; Kaushik & Kaur, 2005; Vergara et al, 2014), although modest heat stress increases cell proliferation and growth (Choudhery et al, 2015; Tounkara et al, 2012). Increasingly, long‐term treatment at subzero temperatures can influence the viability rate of mammalian cells (Jin et al, 2008; Moussa et al, 2008; Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…According to previous studies, low temperature can decrease cell growth rate (Azambuja et al, 1998;Kaushik & Kaur, 2005;Vergara et al, 2014), although modest heat stress increases cell proliferation and growth (Choudhery et al, 2015;Tounkara et al, 2012).…”
Section: Sucrose-based Mediamentioning
confidence: 89%
“…Notably, several studies have demonstrated that increased reactive oxygen species may reduce the stemness of hematopoietic stem cells [ 19 , 20 ] and promote lineage commitment [ 21 ]. In a recent study, it was demonstrated that intracellular reactive oxygen species might be involved in promoting erythroid lineage differentiation of human cord blood CD34+ cells under mild hyperthermia stress condition [ 22 ]. In light of these findings, we propose that the observed erythroid expansion induced by ATO may be mediated by a redox-dependent mechanism that enhances differentiation to the erythroid lineage.…”
Section: Discussionmentioning
confidence: 99%